Pro-Kontra Perspektif Ulama Terhadap Penginvestasian Dana Zakat: studi pendapat ulama - Fauzan, Faisal (Al-Iqtishadiah: Jurnal Hukum Ekonomi Syariah, 2020)
The purpose of this study is to describe these two opinions and the points of their study of the final legal status of investment activities using zakat funds. As a type of library research, this research uses the literature data which concluded two perspectives of ulama that allow and reject investment by using funds from zakat. Results reveal considerations of the view that permits the investment of zakat funds is to take hadith values from Zaid bin Aslam, namely the practice of Rasulullah SAW and Caliph Umar Bin Khattab who made use of the zakat wealth before it was delivered to his mustahik. This opinion also paid attention to the ijtihad or law policy of the caliph Umar bin Khattab who sought the property of orphans, stopped paying zakat for muallaf, and replaced fa'i for the soldiers by giving monthly salaries from Baitul Maal. Opinions that do not allow the investment of zakat funds stand on a hadith from Aisha RA, "Whoever practices a charity that my orders are not given to him, he is rejected". Investing zakat’s assets is considered to inhibit the ownership of zakat by mustahik individually. Whereas zakat has been linked to mustahik ownership rights. Investing zakat funds is considered to have no references and it is feared that this will eliminate the spirit of worship compulsory and potentially zakat changes to be business-oriented.